PROBLEMATIKA PENDIDIKAN MODERASI DALAM PEMIKIRAN WAHBAH AL-ZUHAILI - Zamakhsyari Abdul Majid; Mumun Mulyati (STIT Al-Marhalah Al-Ulya Bekasi, 2022)
ABSTRACTThis paper aims to examine and analyze the problems education of Islamic moderation from the viewpoint of Wahbah al-Zuhaili's Tafsir al-Munir and al-Fiqh al-Islamiy wa Adillatuhu science. The focus of the study in this paper is to analyze the moderate thoughts of Wahbah al-Zuhaili in understanding Islam through Tafsir al-Munir. Wahbah al-Zuhaili as a Muslim intellectual who mastered various scientific disciplines and had a moderate perspective. Wahbah al-Zuhaili's thoughts on moderation in Islamic law through his work al-Fiqh al-Islamiy wa Adilatuhu. In the book of al-Fiqh al-Islamiy wa Adillatuhu, indicators of moderation in Islamic law are a) Flexibility in Islamic Law, b) Renewal in Islamic Law, c) Views in Schools. Keywords: Islamic Moderation, Wahbah al-Zuhaili